Extraction of modal parameters for identification of time-varying systems using data-driven stochastic subspace identification. (October 2018) - Li, Wenchao; Vu, Viet-Hung; Liu, Zhaoheng; Thomas, Marc; Hazel, Bruce
This paper presents a method for the extraction of modal parameters for identification of time-varying systems using Data-Driven Stochastic Subspace Identification (SSI-DATA). In practical applications of SSI-DATA, both the modal parameters and computational ones are mixed together in the identified results. In order to differentiate the structural ones from computational ones, a new method based on the eigen-decomposition of the state matrix constructed in SSI-DATA is proposed. The efficiency of the proposed method is demonstrated through numerical simulation of a lumped-mass system and experimental test of a moving robot for extracting excited natural frequencies of the system.